Time to Rethink Healthcare Research - Nikhat Ahmed Siddiqui (ziauddin University, 2024)
Medical research must translate into improved treatments for patients with advancement in proteomics technology. This will allow us to measure thousands of molecules at a given point in time. These molecules in form of biomarkers give clues about underlying biological processes in health and disease as they are used to monitoring a disease or predict the outcome of a treatment The resulting insights will provide novel drug targets and protein-based markers contributing towards a futuristic basis for personalized medicine.